RELATIONSHIP BETWEEN SHARIA-BASED NURSING SERVICES AND PATIENT LOYALITY AT ISLAMIC HOSPITAL - Dyah Wiji Puspita Sari; Muhammad Abdurrouf; Rismawati Rismawati (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction: Sharia labeled hospitals have more responsibility in providing health services to patients. This challenge requires health care providers to compete by improving the quality of services so that patient loyalty is formed. The purpose of this study was to identify the relationship between sharia-based nursing services and patient loyalty in Semarang Hospital. Methodology: This research is a quantitative type with a cross sectional approach. Data collection using a questionnaire with the number of respondents 105 patients with total sampling technique. Results: the characteristics of respondents mostly consisted of age 36-45 (24.8%), last education elementary school 69 people (65.7%), length of stay that is 4 days a number of 35 people (33.3%), there is a relationship between services sharia-based nursing with patient loyalty at RSISA Semarang with pvalue 0.002 (p-value <0.05) with an R value (0.305). Discussion: This study can be used as a reference in improving good health services by implementing services in accordance with sharia principles so that patient loyalty is achieved.